2014
DOI: 10.1007/s00134-014-3325-5
|View full text |Cite|
|
Sign up to set email alerts
|

Helmet CPAP vs. oxygen therapy in severe hypoxemic respiratory failure due to pneumonia

Abstract: Helmet CPAP reduces the risk of meeting ETI criteria compared to oxygen therapy in patients with severe hARF due to pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
157
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 25 publications
2
157
0
9
Order By: Relevance
“…While noninvasive mechanical ventilatory support by face mask was found to affect neither intubation rates nor clinical outcomes in a randomised controlled trial (RCT) of 123 ARDS patients [5], helmet ventilation was found to reduce the need for intubation when compared to oxygen therapy in a multicentre RCT of 81 ARDS patients [6], and to reduce intubation rates and even to improve survival when compared to a face mask in a single-centre randomised clinical trial of 83 ARDS patients [7]. Oxygen administered through a high-flow nasal cannula is suggested to be an attractive strategy as a first-line therapy to avoid intubation, seen in the results of a multicentre RCT in which 301 hypoxaemic patients without hypercapnia received either high-flow oxygen therapy, standard oxygen therapy delivered through a face mask or noninvasive positive-pressure ventilation [8], but the beneficial effects found thus far need to be confirmed.…”
Section: Noninvasive Versus Invasive Mechanical Ventilation In Patienmentioning
confidence: 95%
“…While noninvasive mechanical ventilatory support by face mask was found to affect neither intubation rates nor clinical outcomes in a randomised controlled trial (RCT) of 123 ARDS patients [5], helmet ventilation was found to reduce the need for intubation when compared to oxygen therapy in a multicentre RCT of 81 ARDS patients [6], and to reduce intubation rates and even to improve survival when compared to a face mask in a single-centre randomised clinical trial of 83 ARDS patients [7]. Oxygen administered through a high-flow nasal cannula is suggested to be an attractive strategy as a first-line therapy to avoid intubation, seen in the results of a multicentre RCT in which 301 hypoxaemic patients without hypercapnia received either high-flow oxygen therapy, standard oxygen therapy delivered through a face mask or noninvasive positive-pressure ventilation [8], but the beneficial effects found thus far need to be confirmed.…”
Section: Noninvasive Versus Invasive Mechanical Ventilation In Patienmentioning
confidence: 95%
“…3 and 4. In patients treated Brambilla, et al 8 Cosentini, et al 9 Squadrone, et al 11 Squadrone, et al (Fig. 4), compared to patients receiving standard oxygen therapy.…”
Section: Effect Of Helmet Cpap On Gas Exchangementioning
confidence: 98%
“…Of these, 304 studies were excluded for the following reasons: 145 duplicate studies; 45 case reports and abstracts; 97 studies without examination of hARF; 15 non-RCTs; one incomplete hARF study carried out by Fasano, et al; 16 and one study by Antonaglia, et al 17 using facial NIV in the control group. Four clinical [8][9][10][11] trials comprising 377 subjects met the inclusion criteria (Table 1). All trials were RCTs, and three of these, were multicenter studies, [9][10][11] and one 9 was a single center study.…”
Section: Search and Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations